(untitled) (Journal of the College of Basic Education, 2023)
The research adopts an attempt to find applied and practical approaches, between the media sign that was included in the ancient Iraqi sculpture and the mechanisms of its operation, and between the mechanisms of the functioning of the media and media material in contemporary globalization, in terms of applications and concepts, and raises a question within the limits of the research, which is whether our ancestors practiced globalization, or What is their idea of it or what was their version of it. The research consists of four chapters, the first of which is concerned with the methodology of the research, represented in presenting its problem, its importance, its objective, and defining the terms.The second chapter came as a representative of the theoretical framework, which consists of two sections: The first topic: globalization.The second topic: Sculpture in ancient Iraq. The third chapter: which included defining the research community and defining the research sample, among these forms, which included five models, and sample analysis.While the fourth chapter came to record the results of the research, the researcher’s conclusions, and his recommendations, and the most important results of the research are the following: 1-The ruling authority throughout the ages has media tools that spread the local media culture that this authority adopts or believes in, through the channels available to it to the world. 2-Mesopotamia civilization spread among the nations of the ancient world with the primacy of knowledge. 3-The old Iraqi media machine was superior and effective in the ancient world. 4-The media institution of the ancient civilization of Iraq relied on all kinds of sculpture to achieve influence and sovereignty in the ancient world. 5-The media mechanisms in the ancient civilization of Iraq, through their various arts, especially the art of sculpture, were able to spread their knowledge globally in the ancient world through direct and indirect influence on most of the civilizations of the ancient world, and such influence is still effective in the present day.